PENERAPAN MANIPULATING FABRIC CREPING PADA EVENING GOWN DAN ACCESSORIES - Karina, Andani Warda; Wahyuningsih, Urip (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
The aim of the research is to find out the results of applying manipulating fabric creping to Evening Gowns and Accessories. Using organza and duces fabric as the main material. Inspired by the source of the idea taken. The process of applying manipulating fabric creping begins with determining the application of manipulating creping on the evening gown, after which the manipulating is made using marble binding and boiling techniques. The silhouette used in this clothing is the L silhouette, namely the shape of a wide mermaid dress at the bottom, and is equipped with accessories. The application of manipulating fabric creping is found on the sleeves, body of the clothing and accessories, giving a unique and boldly different impression. This research uses the double diamond model research method which has 4 stages, namely discover, define, develop, and deliver. The result of this research is the application of manipulating creping on evening gowns and accessories.